2020
DOI: 10.3390/ijms21155295
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Roles and Applications of Immunoglobulins in Neurodegenerative Disease

Abstract: Natural autoantibodies, immunoglobulins (Igs) that target self-proteins, are common in the plasma of healthy individuals; some of the autoantibodies play pathogenic roles in systemic or tissue-specific autoimmune diseases, such as rheumatoid arthritis and systemic lupus erythematosus. Recently, the field of autoantibody-associated diseases has expanded to encompass neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), with related studies examining the functions of Igs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 137 publications
(174 reference statements)
1
11
0
Order By: Relevance
“…This point is further corroborated by the fact that serum autoantibodies alone might occur in healthy humans that do not reveal cognitive decline, as a study by Levin demonstrated (Levin et al 2010 ). In addition, autoantibodies may not even contribute to the disease progress and pathophysiology, as they can play a protective role, i.e., specific autoantibodies in Alzheimer’s disease (Sim et al 2020 ). Another relevant issue is that the presence of serum autoantibodies seems to depend on the blood–brain barrier’s integrity, as its breakdown is accompanied by the numerous and highly varied human brain reactive autoantibodies targeting membrane proteins (Levin et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This point is further corroborated by the fact that serum autoantibodies alone might occur in healthy humans that do not reveal cognitive decline, as a study by Levin demonstrated (Levin et al 2010 ). In addition, autoantibodies may not even contribute to the disease progress and pathophysiology, as they can play a protective role, i.e., specific autoantibodies in Alzheimer’s disease (Sim et al 2020 ). Another relevant issue is that the presence of serum autoantibodies seems to depend on the blood–brain barrier’s integrity, as its breakdown is accompanied by the numerous and highly varied human brain reactive autoantibodies targeting membrane proteins (Levin et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vascular-derived anti-neuronal autoantibodies contained in specific brain neurons with degenerative and apoptotic features, including C1q and C5b-9 complement compounds and the permeable blood brain barrier, suggest autoimmunity-induced cell death in AD [ 112 ]. More specifically, autoantibodies targeting FcγR-mediated function, tau and ceramide in AD or FcγR-mediated function in PD, were observed to be pathogenic [ 113 ]. Most recently, putative 16 autoantibody biomarkers were detected in the cerebrospinal fluid of AD [ 114 ] So, not surprising is the above mentions gluten-brain cross-reactivity [ 8 , 9 , 10 , 78 , 79 ] and sequence homology between gluten/gliadin peptides and cephalic epitopes ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The arrival of peripheral immune cells at the CNS may have a role in modulating these microglial functions such that subsequent stimuli produce exaggerated responses, and thus affect the outcome in CNS injury and disease (Prinz and Priller, 2017 ; Greenhalgh et al, 2020 ; Urban et al, 2020 ). All lines of evidence provided, it might be speculated that a key trigger to PD pathogenesis is the peripheral immune system that could affect the neuroinflammation of CNS to induce and promote the process of PD (Sim et al, 2020 ). In this study, using high throughput data and bioinformatic techniques, we provided more robust evidence for the potential roles of infiltrating immunocytes in PD as well as their key molecules, which might be helpful to further illustrate the correlations between the peripheral immune system and PD.…”
Section: Discussionmentioning
confidence: 99%